2018
DOI: 10.5812/jhealthscope.62319
|View full text |Cite
|
Sign up to set email alerts
|

Informal Payments for Inpatient Services and Related Factors: A Cross-Sectional Study in Tehran, Iran

Abstract: Background: Informal payments, as one of the components of out-of-pocket (OOP) payments, are often a form of corruption and outside the official bill. The purpose of the present study was to investigate the frequency of informal payments for inpatient services and its related factors in Tehran, Iran. Methods: In this cross-sectional study, the samples included 450 patients who were admitted to hospital's clinics affiliated to Shahid Beheshti University of Medical Sciences in Tehran, to receive follow-up and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…We think that parents are perhaps more willing to pay for their children, and when paying for themselves, they may have more time in circumventing the providers who may demand informal payments, and may use services in which informal payments are less common. The evidence on the effect of age on IPs is mixed [25,27,34,35]. For example, Meskarpour-Amiri et al reported that the elderly are at increased risk of paying informally for health care, while Zarei et al found no significant relationship between the IPs behaviour and the patient's age.…”
Section: Policy Advocacymentioning
confidence: 99%
See 1 more Smart Citation
“…We think that parents are perhaps more willing to pay for their children, and when paying for themselves, they may have more time in circumventing the providers who may demand informal payments, and may use services in which informal payments are less common. The evidence on the effect of age on IPs is mixed [25,27,34,35]. For example, Meskarpour-Amiri et al reported that the elderly are at increased risk of paying informally for health care, while Zarei et al found no significant relationship between the IPs behaviour and the patient's age.…”
Section: Policy Advocacymentioning
confidence: 99%
“…Some of them reported that living in the rural areas increased the likelihood of paying IPs [7], while others stated that living in an urban area and large cities increased the probability of paying IPs [37]. In addition, there is some evidence showing no significant relationship between IPs and the place of the patient's residence [28,30,35,38]. Our study provided evidence to confirm that those living in large cities are at increased risk of paying informally for inpatient health care services.…”
Section: Policy Advocacymentioning
confidence: 99%
“…However, the improper adaptation of the tariffs, manipulating and involving some intentional changes in the relative values of healthcare services, caused moving tariff values away from the actual fiscal values of the health services. During the last years, irrational medical tariffs have caused some health professionals to request informal patients payments or attempt to get high revenues [47,48]. The dissatisfaction of some stakeholders with tariffs has also produced different viewpoints about continuation or discontinuation of California book values as a reference point for tariff setting.…”
Section: Major Shortfalls and Drawbacks Brought By The Implementationmentioning
confidence: 99%
“…However, the improper adaptation of the tariffs, manipulating and involving some intentional changes in the relative values of healthcare services, caused moving tariff values away from the actual scal values of the health services. During the last years, irrational medical tariffs have caused some health professionals to request informal patients payments or attempt to get high revenues [48,49]. The dissatisfaction of some stakeholders with tariffs has also produced different viewpoints about continuation or discontinuation of California book values as a reference point for tariff setting.…”
Section: Major Shortfalls and Drawbacks Brought By The Implementationmentioning
confidence: 99%